EVOLUTION OF SPATIAL COMPLEXITY IN ROMANIA: NETWORKING, DIFFERENTIATION - PAUL-RĂZVAN ŞERBAN (Revue Roumaine de Géographie)
The spatial complexity is negatively correlated with regional specialization. Demonstration of how regional specialization has been evolving has relevance in studying the dynamics of spatial complexity. The organization of phenomena has been studied starting with O. Onicescu’ research of entropy measurement using Information Energy Index based on the sum of squared frequency of components. Entering this index data indicating the share of employment in key sectors of the economy we noticed that an important feature of complex systems is their tendency to increase their own complexity. It has been observed that processes of complex systems tend to develop complexity. Thus,complexity in nature is increasing. Many researchers are convinced that self-powering increasing complexity isan obvious fact, not without consequences - mainly because it sometimes leads to imbalances in the development of various system components that will not go unnoticed in the dynamics of the system as a whole.